Dinar/Dirham Backed Electronic Payment System For Malaysian Market - Mohd Nazri Muhayiddin; Elsadiq M.A. (2009)
In addition to highlighting repeated failures of previous fiat currency systems, this paper also takes a different approach of revealing the fine performance of gold i.e. as far as its purchasing power is concerned. This study calculates the price of a few inflationary items in terms of Ringgit Malaysia (RM), as well as their corresponding prices in terms of gold (or silver). Having convinced with a fine performance of gold in terms of its purchasing power, it is therefore the aim of this paper to solve the problem of “portability” inherited in gold. If gold were to be adopted successfully as a payment system, the issue of portability should be correctly addressed or else the masses would not be encouraged to use it. Specifically, this paper proposes the use of e-commerce technology in order solve the portability problem in gold (or silver). Other “physical constraints” associated with the two precious metals can also be solved through the proposed e-commerce system. Apart from that, empirical studies will also be done on currently operated electronic payment systems in order to study the willingness of Malaysian people to adopt a new payment system.